PENERAPAN TROLI ANGKUT ERGONOMI PADA PEMINDAHAN BAHAN BAKU ADONAN BATA MERAH DI UMKM KALIWUNGU KUDUS UNTUK MENINGKATKAN PRODUKTIVITAS - Vikha Indira Asri; Adhie Prayogo; Dina Lusianti (Aplikasia: Jurnal Aplikasi Ilmu-ilmu Agama, 2025)
Government support and related parties is very necessary for MSMEs who often face challenges such as limited capital, market access and technology, to increase competitiveness and sustainability.. The application of ergonomic technology in the production process can increase efficiency and productivity, especially in small and medium industries (SMEs). This PKM aims to implement ergonomic trolleys in the red brick making process at UMKM Kaliwungu, Kudus, in order to reduce physical workload and increase productivity. The method used in this PKM uses a quantitative method by providing assistance and counseling on ergonomic aspects in the design of production aids through four stages, namely partner situation analysis, partner problem identification, PKM implementation and evaluation of PKM implementation. The results of the study showed that the use of ergonomic trolleys was able to increase the efficiency of transporting raw materials by 27.59% and reduce the risk of injury due to repetitive manual activities. In addition, productivity increased by 38.15% after the implementation of ergonomic trolleys. Positive impacts were also felt by workers who claimed to be more comfortable and less tired while working